2010
DOI: 10.5194/acp-10-2353-2010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution of volatile organic compounds in the outflow of the Mexico City Metropolitan area

Abstract: Abstract. The volatile organic compound (VOC) distribution in the Mexico City Metropolitan Area (MCMA) and its evolution as it is uplifted and transported out of the MCMA basin was studied during the 2006 MILAGRO/MIRAGEMex field campaign. The results show that in the morning hours in the city center, the VOC distribution is dominated by non-methane hydrocarbons (NMHCs) but with a substantial contribution from oxygenated volatile organic compounds (OVOCs), predominantly from primary emissions. Alkanes account f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 77 publications
8
127
2
1
Order By: Relevance
“…In Table 3 we report both the 1-sigma uncertainty in the regression slope and the calibration uncertainty. We note that the emission ratios presented here for ethane and propane differ substantially from those calculated by Apel et al (2010), which were derived from lsided linear regression fits. Because of the poor correlation of ethane and propane with CO, their ratios versus CO have a limited value and a very large uncertainty.…”
Section: Hydrocarbonsmentioning
confidence: 58%
See 2 more Smart Citations
“…In Table 3 we report both the 1-sigma uncertainty in the regression slope and the calibration uncertainty. We note that the emission ratios presented here for ethane and propane differ substantially from those calculated by Apel et al (2010), which were derived from lsided linear regression fits. Because of the poor correlation of ethane and propane with CO, their ratios versus CO have a limited value and a very large uncertainty.…”
Section: Hydrocarbonsmentioning
confidence: 58%
“…Here, these measurements are compared with canister sample analyses and with proton-transfer-reaction mass spectrometry (PTR-MS) measurements made from the Aerodyne mobile laboratory and from the US Department of Energy G1 aircraft. Because the Aerodyne mobile laboratory and the G1 aircraft also sampled near other surface sites and because canister samples were collected at many surface sites and from the NASA DC-8 and NCAR C-130 aircraft, these comparisons can be used to evaluate the consistency of VOC data obtained throughout the campaign (Kleinman et al, 2008;Fortner et al, 2009;Karl et al, 2009;Apel et al, 2010). In addition, this study supplements our understanding of the specificity of proton-transfer-reaction mass spectrometry (PTR-MS) measurements in a dense megacity with a complex VOC composition that challenges the analytical capabilities of this technique (de Gouw and Warneke, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of enhancement ratios, many hydrocarbon species relative to CO were higher in Mexico City than in the US Apel et al, 2010), and similar enhancement ratios were found for most oxygenated VOCs ). The higher hydrocarbon enhancement ratios in Mexico City compared to the US are due to the widespread use of LPG and higher industrial and evaporative emissions of aromatics.…”
Section: Voc Distributions and Patternsmentioning
confidence: 81%
“…HONO was measured using the Long-Path Absorption Photometer (LOPAP) technique described in Villena et al (2011) with a reported 10 % measurement uncertainty. Finally, a large suite of organic compounds was measured both in situ by fast GC-MS (Apel et al, 2010) and via whole air canister samples with offline GC-MS (Russo et al, 2010). Those species that were directly used in this analysis are listed in Table 5.…”
Section: R Thompson Et Al: Interactions Of Bromine Chlorine Anmentioning
confidence: 99%